Removal of concentrated Cr(III) from real tannery wastewater using abiotic and anaerobic processes with native microbial consortia. Issue 1 (February 2021) - Reyes-Romero, Brandon; Gutiérrez-López, Adriana N.; Hernández-Altamirano, Raúl; Mena-Cervantes, Violeta Y.; Ruiz-Baca, Estela; Neri-Torres, Elier E.; Chairez, Isaac; García-Solares, Selene M.; Vazquez-Arenas, Jorge
Graphical abstract: Highlights: Cr (III) removal sequentially occurs in abiotic and biotic stages. Cr(III) bioremoval using isolated microbial consortia under anaerobic conditions. Inoculum of bacteria improves tolerance for high Cr (III) concentrations. Bioaccumulation/biotransformation as synergistic Cr(III) removal mechanisms. Native consortia made up of Lactobacillus diolivorans and Lactobacillus brevis . Abstract: Microbial consortia are isolated and enriched in discontinuous reactors under anaerobic conditions using different stoichiometric ratios of acetate (substrate): Cr(III) concentration: reactors A (0.5:1), B (1:1) and C (2:1). The inoculum is stemmed from a tannery effluent with the aim of tolerating and eliminating high concentrations of Cr(III) (2760 mg L −1 ). The Cr(III) removal process is performed in two stages for each reactor. Stage I is an abiotic process involving the reaction between acetate and Cr(III) forming the complex C r H 2 O x C H 3 C O O y 3 - y, which on its turn precipitates as C r 2 O 3 ( s ) in the first five days, thus, decreasing the metal concentration by 24, 42 and 61 % for reactors A, B and C respectively. FT-IR analysis, SEM-EDX, biomass and extracellular polymeric substances (EPS) indicate that the native bacteria enriched in the reactors eliminate Cr (III) during the biotic stage via bioadsorption and bioaccumulation mechanisms. Reactor C achieved the lowest Cr(III) concentration around 600 mg L -1 (78 % removal). The occurrence of these mechanisms was due to the nature of the inoculum since the bacteria were well adapted to the presence of high Cr(III) concentrations, whereby they did not require optimal growth conditions unlike a pure strain. The isolated strains were molecularly identified by amplification and sequencing of the 16 s rRNA gene using universal oligos 63 F (5'CAGGCCTAACACATGCAAGTC3′) and 1542R (5′AAGGAGGTGATCCAGCCGCA3′), finding a 99.06 % of similarity to Lactobacillus diolivorans (strain JCM 12183 accession number LC311745.1), and 99.88 % similarity to Lactobacillus brevis (strain C23 accession number MN880215.1). SEM-EDX enables to identify that the consortia are mainly composed of bacilli undergoing pleomorphism, due to the complex formations between functional groups in the cell wall and Cr(III).